Prevalence and clinical potential of extraspinal incidental findings in lumbosacral spine MRI of patients with suspected disc diseases (Faculty of Medicine Universitas Indonesia, 2021)
BACKGROUND Incidental findings could be observed in organs close to the spine while reporting lumbosacral spine magnetic resonance imaging (MRI). This study aimed to report the prevalence and clinical potential of extraspinal incidental findings in lumbosacral MRI of patients with suspected disc diseases. METHODS This single-centered cross-sectional study was carried out on 420 consecutive adult patients who underwent lumbar spine MRI for suspected disc disease from January to July 2019. The MRI was checked for the presence of extraspinal incidental findings, and each finding was categorized according to the body organ and its clinical significance. Each MRI plane that best displayed the findings was recorded, and the association between the findings and patient's age and sex was determined. RESULTS Of 420 samples, 135 cases showed extraspinal findings (32.1%), and 7.6% of the patients displayed suspicious lesions. The urinary tract was the most common system (18.6%) to display both clinically significant (5.0%) and benign findings (13.6%), and the axial MRI section was the plane which showed most of the incidental findings. Incidental findings in any body system were rarely found in the younger patients. Females had significantly higher benign findings than males (p = 0.002). CONCLUSIONS The prevalence of extraspinal findings in lumbosacral spine MRI is high, and some are significant. Most findings are related to the urinary tract and best displayed in the axial plane.